Q-HAM: a multicenter upfront randomized phase II trial of quizartinib and high-dose Ara-C plus mitoxantrone in relapsed/refractory AML with FLT3-ITD - Jaramillo Segura, Sonia; Le Cornet, Lucian; Kratzmann, Markus; Krisam, Johannes; Görner, Martin; Hänel, Mathias; Röllig, Christoph; Wass, Maxi; Scholl, Sebastian; Ringhoffer, Mark; Reichart, Alexander; Steffen, Björn; et al. (Trials, 2023)
Background: About 50% of older patients with acute myeloid leukemia (AML) fail to attain complete remission (CR) following cytarabine plus anthracycline-based induction therapy. Salvage chemotherapy regimens are based on high-dose cytarabine (HiDAC), which is frequently combined with mitoxantrone (HAM regimen). However, CR rates remain low, with less than one-third of the patients achieving a CR. FLT3-ITD has consistently been identified as an unfavorable molecular marker in both relapsed and refractory (r/r)-AML. One-quarter of patients who received midostaurin are refractory to induction therapy and relapse rate at 2 years exceeds 40%. The oral second-generation bis-aryl urea tyrosine kinase inhibitor quizartinib is a very selective FLT3 inhibitor, has a high capacity for sustained FLT3 inhibition, and has an acceptable toxicity profile. Methods: In this multicenter, upfront randomized phase II trial, all patients receive quizartinib combined with HAM (cytarabine 3g/m2 bidaily day one to day three, mitoxantrone 10mg/m2 days two and three) during salvage therapy. Efficacy is assessed by comparison to historical controls based on the matched threshold crossing approach with achievement of CR, complete remission with incomplete hematologic recovery (CRi), or complete remission with partial recovery of peripheral blood counts (CRh) as primary endpoint. During consolidation therapy (chemotherapy and allogeneic hematopoietic cell transplantation), patients receive either prophylactic quizartinib therapy or measurable residual disease (MRD)-triggered preemptive continuation therapy with quizartinib according to up-front randomization. The matched threshold crossing approach is a novel study-design to enhance the classic single-arm trial design by including matched historical controls from previous clinical studies. It overcomes common disadvantages of single-armed and small randomized studies, since the expected outcome of the observed study population can be adjusted based on the matched controls with a comparable distribution of known prognostic and predictive factors. Furthermore, balanced treatment groups lead to stable statistical models. However, one of the limitations of our study is the inability to adjust for unobserved or unknown confounders. Addressing the primary endpoint, CR/CRi/CRh after salvage therapy, the maximal sample size of 80 patients is assessed generating a desirable power of the used adaptive design, assuming a logistic regression is performed at a one-sided significance level α=0.05, the aspired power is 0.8, and the number of matching partners per intervention patient is at least 1. After enrolling 20 patients, the trial sample size will be recalculated in an interim analysis based on a conditional power argument. Conclusion: Currently, there is no commonly accepted standard for salvage chemotherapy treatment. The objective of the salvage therapy is to reduce leukemic burden, achieve the best possible remission, and perform a hemopoietic stem-cell transplantation. Thus, in patients with FLT3-ITD mutation, the comparison of quizartinib with intensive salvage therapy versus chemotherapy alone appears as a logical consequence in terms of efficacy and safety. Ethics and dissemination: Ethical approval and approvals from the local and federal competent authorities were granted. Trial results will be reported via peer-reviewed journals and presented at conferences and scientific meetings. Trial registration: ClinicalTrials.gov NCT03989713; EudraCT Number: 2018-002675-17.